Analysis of the effect of different withering methods on tea quality based on transcriptomics and metabolomics - Jia, Xiaoli; Zhang, Qi; Chen, Meihui; Wang, Yuhua; Lin, Shaoxiong; Pan, Yibin; Cheng, Pengyuan; Li, Mingzhe; Zhang, Ying; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2023)
Withering is very important to the quality of Wuyi rock tea. In this study, transcriptome and metabolomics were used to analyze the effects of different withering methods on tea quality formation. The results showed that sunlight withering (SW) was most beneficial in increasing the gene expression of ubiquinone and other terpenoid-quinone biosynthesis (ko00130), pyruvate metabolism (ko00620), starch and sucrose metabolism (ko00500), and tryptophan metabolism (ko00380) pathways, and increasing the content of nucleotides and derivatives, terpenoids, organic acids and lipids, thus enhancing the mellowness, fresh and brisk taste and aroma of tea. Withering trough withering (WW) was most beneficial in increasing the gene expression of glutathione metabolism (ko00480), phenylpropanoid biosynthesis (ko00940) pathway, increasing the content of phenolic acids and flavonoids, thus enhancing tea bitterness. A comprehensive evaluation of the metabolite content and taste characteristics of tea leaves showed SW to be the best quality and charcoal fire withering (FW) to be the worst quality. This study provided an important basis for guiding the processing of Wuyi rock tea with different flavors.